A diplomática contemporânea: na identificação da tipologia documental da Igreja Evangélica Maranata - PEREIRA, Elayne Cristina da Silva (2017)
Aiming at a future Documentary Management in the religious institution, the possible performance of Archives and the need of the archivist in this kind of collection, in this study was analyzed the Contemporary Diplomacy, as a parameter of identification of the typologies produced by the Evangelical Church Maranata and the way of these documents are produced. As a way of understanding the work of the Contemporary Diplomatic and its relation with the Archivist, was traced its trajectory from the antiquity until the 21st century to show how the Diplomatic Contemporary is structured and its functionality. Also showing the correlation of the Contemporary Diplomatic with the Documentary Typology as methods of Archival Identification. The standard of diplomatic analysis, proposed by the author Tognoli (2013), as a basis for analysis of the documentary typologies, was used three documentary typologies: Minutes of meeting, Term of Commitment and Responsibility and Form for credential Of Pastor. Was applied the diplomatic analysis and were attested to the possibility of the archivist, but in a basic way, through the obtained results.